1995
DOI: 10.1074/jbc.270.4.1636
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Resonance Raman Studies of Quaternary Structure of Hemoglobin Using a Tryptophan β37 Mutant

Abstract: Environmental changes of tyrosine and tryptophan residues of hemoglobin (Hb) upon its T to R transition of quaternary structure were investigated with ultraviolet resonance Raman (UVRR) spectroscopy excited at 235 nm. DeoxyHb A (T-form) showed a UVRR spectrum distinctly different from those of the ligated Hbs (R-form) including oxyHb, COHb, and metHb A, whereas the ligated Hbs exhibited similar UVRR spectra irrespective of the ligand species and the oxidation state of the heme. To characterize the spectral cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 28 publications
5
74
0
Order By: Relevance
“…44 interface, its UVRR intensity is particularly sensitive to the quaternary structure. 33 The W17 band is sensitive to hydrogen bonding of the NH part of the indole side chain. 1 In fact, the W17 frequency of a-lactalbumin exhibits an upshift upon exposure of Trp to the solvent.…”
Section: Tryptophan-related Modesmentioning
confidence: 99%
“…44 interface, its UVRR intensity is particularly sensitive to the quaternary structure. 33 The W17 band is sensitive to hydrogen bonding of the NH part of the indole side chain. 1 In fact, the W17 frequency of a-lactalbumin exhibits an upshift upon exposure of Trp to the solvent.…”
Section: Tryptophan-related Modesmentioning
confidence: 99%
“…The deoxy-HbA minus CO-HbA solution phase UVRR difference spectrum (Fig. 1b) is primarily reflective of changes in the R-T sensitive ␣ 1 ␤ 2 dimer interface arising from differences between the deoxy T and liganded R conformations (7,(23)(24)(25)(26)(27)(28)(29). The W3 difference feature at 1549 cm Ϫ1 (Fig.…”
Section: Ligand Binding To Sol-gel Encapsulated Hemoglobin 30358mentioning
confidence: 99%
“…1b) on the low frequency side of the central peak at 1559 cm Ϫ1 (Fig. 1a) originates from a T-R conformational difference in Trp␤37, the pivotal residue in the hinge region of the ␣ 1 ␤ 2 interface (7,23,26,28). Whereas Trp␤37 is responsible for the low frequency shoulder of the W3 band, Trp␣14 and Trp␤15, located on the A helices, are the source of the central W3 peak at 1559 cm Ϫ1 (7,21).…”
Section: Ligand Binding To Sol-gel Encapsulated Hemoglobin 30358mentioning
confidence: 99%
“…Studies of Hb Hirose ( 37Trp f Ser) (16) and Hb Rothchild ( 37Trp f Arg) (14) have indicated that the change of Trp UVRR bands was ascribed to 37Trp. n the other hand, the spectral changes of Tyr UVRR bands were interpreted to arise from hydrogen bond formation between R42Tyr and 99Asp upon the R-T quaternary transition (14).…”
mentioning
confidence: 97%